'It's a powerful message': a qualitative study of Australian healthcare professionals' perceptions of asthma through the medium of drawings. Issue 4 (25th April 2019) - Cheung, Melissa Mei Yin; Saini, Bandana; Smith, Lorraine
Abstract : Objectives: This study aimed to explore healthcare professionals' (HCPs') perspectives of asthma through their drawings, and their responses when viewing patients' drawings of their experiences of asthma. Design: A qualitative exploratory study with a purposive, convenience sample of participants. Participants were asked to first express their perspectives of asthma in a drawing, which was followed by a review of drawings made by patients with asthma. Setting: Primary and tertiary HCPs from Sydney, Australia. Participants: Twenty-three HCPs from a range of health professions. Results: The HCPs illustrated their perspective of asthma through drawings which were largely biomedically framed, depicting physiological and clinical aspects of asthma. In contrast, their discussion around the patients' drawings centred on the person more than the condition. The patients' drawings triggered the HCPs to revisit their personal expectations of their patients' illness experience; prompted differing degrees of acknowledgement and empathy regarding the patient experience; and encouraged clinical reflexivity. Conclusions: Our findings provide support for the educational application of patients' drawings in bringing HCPs closer to the patient lived experience. The drawings fostered deeper insight into patient perspectives of asthma and stimulated critical reflection on current healthcare practices.